State of health : pleasure and politics in Venezuelan health care under Chávez - Cooper, Amy, 1976- (University of California Press, 2019)
"State of Health: Pleasure and Politics in Venezuelan Health Care under Chávez takes readers inside one of the most controversial regimes of the 21st century for an in-depth account of how poor people's lives changed when the state reorganized its health system. This lively and accessible ethnography looks at the pleasure people took in new features of government health care such as personalized doctors' visits, health activism, and therapeutic dancing. Based on extensive participant observation and interviews, this book shows that government health care in revolutionary Venezuela excited people because it provided more than medicine. Health programs empowered and affirmed poor people as valued members of society, making it clear that their lives mattered. This book explains the meanings of socialized medicine from the vantage point of historically marginalized Venezuelans, who made up the majority of the country's population. It offers a singularly unique account of daily life in Chávez's Venezuela. Although people's lives have changed dramatically since the Chávez era, this book provides lasting insights into how ordinary people experience radical moments of social and political change. State of Health signals a paradigm shift in the field of medical anthropology by establishing the value of studying pleasure with the same seriousness of purpose with which ethnographers study suffering. This book shows how paying more attention to the positive aspects of medicine could revolutionize our understanding of how health care gives meaning to people's lives"--Provided by publisher.